2015
DOI: 10.1089/ees.2014.0129
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Flue Gas Desulfurization Gypsum Amendments on Heavy Metal Distribution in Reclaimed Sodic Soils

Abstract: Although flue gas desulfurization (FGD) gypsum has become an effective soil amendment for sodic soil reclamation, it carries extra heavy metal contamination into the soil environment. The fate of heavy metals introduced by FGD gypsum in sodic or saline-alkali soils is still unclear. This work aims to investigate the effects of FGD gypsum addition on the heavy metal distributions in a sodic soil. Original soil samples were collected from typical sodic land in north China. Soil column leaching tests were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The concentrations of all the metals in the treated plots were well below the risk control standard for soil contamination of agricultural land in China MEEPRC (Ministry of Ecology and Environment of the People's Republic of China), 2018. Similar results were reported in our previous studies (Chen et al, 2015;Zhao et al, 2018aZhao et al, , 2018b and other studies (Koralegedara et al, 2017;Sakai, Matsumoto, & Sadakata, 2004) in both laboratory soil columns and field experiments.…”
Section: Soil Heavy Metalssupporting
confidence: 92%
See 1 more Smart Citation
“…The concentrations of all the metals in the treated plots were well below the risk control standard for soil contamination of agricultural land in China MEEPRC (Ministry of Ecology and Environment of the People's Republic of China), 2018. Similar results were reported in our previous studies (Chen et al, 2015;Zhao et al, 2018aZhao et al, , 2018b and other studies (Koralegedara et al, 2017;Sakai, Matsumoto, & Sadakata, 2004) in both laboratory soil columns and field experiments.…”
Section: Soil Heavy Metalssupporting
confidence: 92%
“…Ca, S, K and B) and increase crop yields (Clark et al, 2001). In addition, the impurities and heavy metals in FGD gypsum and their potentially hazardous effects on plants and water after its application to soils have been studied extensively (Chen et al, 2015;Ishak, Seaman, Sumner, & Miller, 1999;Yang et al, 2016). In general, most studies have confirmed that the use of FGD gypsum in agriculture presents a relatively small ecological risk (Briggs, Fine, Markee, & Gustin, 2014;Sakai et al, 2004;Wang et al, 2008) and even helps remove trace elements from soils (Clark et al, 2001;Koralegedara et al, 2017).…”
mentioning
confidence: 99%
“…Biochar materials strongly sorb polycyclic aromatic hydrocarbons (PAHs) and are thus characterized by very high sorption coefficients (K D ) for PAHs [27].It was also reported that the N loss was mitigated by adding FGD gypsum to composting materials [28,29]. Flue gas desulphurization gypsum (FGD gypsum) is a by-product of wet gas desulphurization in coal-fired power stations and generally has a high purity, low heavy metal content, and is rich in essential mineral nutrients for plants such as S, Si and Ca [30,31]. The volatilization of ammonia and N loss were reduced by combining organic N-rich organic waste with FGD gypsum during the composting process [29].…”
mentioning
confidence: 99%
“…Gypsum has been known as an effective product used in the remediation of sodic soils, by greatly reducing the exchangeable Na, K, and Mg cation concentrations in the sodic soils [32,33]. Approximately 1-2 wt % of FGD gypsum was used to reclaim the sodic soil which resulted in no obvious heavy metal contamination [31]. Guo et al [30] suggested adding 10% FGD gypsum to compost material to reduce nitrogen loss during composting.…”
mentioning
confidence: 99%
“…The key to the improvement of saline-soil is the reduction of soil ESP. FGD-gypsum reducing soil ESP is due to that, calcium ion's flocculation ability for soil clay is superior to that of sodium ion [6], calcium ion from FGDgypsum could replace exchangeable sodium in soil colloids, then soil ESP is reduced [22].…”
Section: Soil Alkalinitymentioning
confidence: 99%